Analisis Penerapan Rencana Keselamatan Konstruksi (RKK) Terhadap Mutu Pada Proyek Gedung - Aceng Kurniawan (JURNAL ILMIAH NUSANTARA, 2024)
This research aims to determine the evaluation of the implementation of the construction safety plan (RKK) on quality performance, the researcher chose the UGM Faculty of Medicine, Public Health and Nursing Microbiology Building Construction Project, and analyzed the dominant factors that influence the implementation of the Construction Safety Plan (RKK) in the UGM Microbiology Building project . This research uses quantitative methods with multiple linear regression analysis. The population in this study were all employees and workers of the UGM FKKMK Microbiology Building Construction Project. The research results show that the level of RKK implementation on project quality shows a positive and significant influence, with a very strong correlation value of 0.722. This shows that the RKK is implemented effectively in this project. The results of the dominant test analysis show that the dominant factors that influence based on the results of the analysis, Supervision and Audit are the dominant factors that most influence the implementation of the Construction Safety Plan and the quality of the UGM Microbiology Building project, with contributions amounting to 30.1%. Supervision and audit are the dominant factors that most influence the implementation of the RKK and project quality with the largest contribution of 30.1%.